Biochar synergistic multi-source solid waste modified red gypsum roadbed material and preparation method thereof
By synergistically interacting biochar, blast furnace slag, red mud and red gypsum, modified red gypsum roadbed materials are prepared, which solves the problems of long settling time and low compressive performance of roadbed materials in the existing technology, and achieves higher water resistance and compressive resistance to meet engineering needs.
Patent Information
- Application Number
- CN202411630899.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-07
AI Technical Summary
It is difficult to prepare a mixed subgrade material in the prior art, which can improve mechanical strength and water resistance while shortening the settling time and meet engineering needs.
By synergistically interacting biochar, blast furnace slag, red mud and red gypsum, a biochar synergistic multi-source solid waste modified red gypsum roadbed material is prepared, which optimizes the performance of red gypsum, shortens the settling time, improves compressive performance and water resistance. sex.
It has achieved the shortening time of the subgrade material, improved the compactness of its internal structure, enhanced water resistance and compressive resistance, and met the requirements of road base construction.
Smart Images

Figure CN119390419A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ecological environment protection and solid waste resource utilization, and specifically relates to a biochar-synergistic multi-source solid waste-modified red gypsum roadbed material and a preparation method thereof. Background Art
[0002] In recent years, along with the rapid economic growth of my country, highway construction has developed rapidly. Roadbed is the foundation of highway, and roadbed filling requires a large amount of soil or stone resources. With the implementation of national environmental protection policies, in order to protect green waters and green mountains, excessive exploitation of natural soil and stone resources is strictly prohibited. Due to the large number of engineering construction projects, large material demand, and serious over-exploitation in some areas, they are facing the problem of scarce roadbed filling material resources. Red gypsum is a waste material from titanium dioxide production. Every 1t of titanium dioxide produced will emit 5t of red gypsum. It is rich in dihydrate gypsum and hemihydrate gypsum and can be used to generate cementitious materials, but due to its low activity, it is difficult to use on a large scale, resulting in large-scale stockpiling, which poses the risk of occupying land resources and polluting the environment.
[0003] However, directly using red gypsum as a roadbed material has the problems of low compressive strength and long setting time, which cannot meet the engineering requirements. Therefore, how to prepare a mixed roadbed material that can alleviate the long setting time while improving mechanical strength and water resistance.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a biochar synergistic multi-source solid waste modified red gypsum roadbed material. The biochar synergistic multi-source solid waste modified red gypsum roadbed material synergizes the biochar, blast furnace slag, red mud and red gypsum to greatly shorten the coagulation time and make the internal structure of the modified red gypsum roadbed material more compact, with higher water resistance and compression resistance, which can well meet the requirements of road base construction.
[0006] The second purpose of the present invention is to provide a method for preparing a biochar-synergistic multi-source solid waste-modified red gypsum roadbed material, which crushes and pyrolyzes biomass to obtain biochar with surface functional groups and a porous structure, and optimizes the red gypsum through the biochar-synergistic multi-source solid waste to prepare a roadbed material with better water resistance and higher compressive resistance.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: Biochar synergistic multi-source solid waste modified red gypsum roadbed material, characterized in that it mainly includes biochar, blast furnace slag, red mud, red gypsum, cement and water; The mass ratio of biochar, blast furnace slag, red mud, red gypsum and cement is (1-5): (1-10): (60-70): (1-5); The mass ratio between the mixture of biochar, blast furnace slag, red mud, red gypsum and cement and water is 1: (0.6-0.8).
[0008] Preferably, as a further specific implementation, the mass ratio of the biochar, blast furnace slag, red mud, red gypsum and cement is 3:10:10:70:5; The mass ratio between the mixture of biochar, blast furnace slag, red mud, red gypsum and cement and water is 1:0.6.
[0009] In the preparation process of the roadbed material of the present invention, the chemical reaction between cement and water, namely the hydration reaction, is the key to determining the strength of the roadbed material. When the cement particles come into contact with water, the clinker minerals on their surfaces will immediately undergo hydrolysis or hydration with water to generate a new hydration product. There are rate differences in the hydration reactions produced by various minerals and water. When tricalcium silicate is hydrated to generate hydrated calcium silicate gel and calcium hydroxide crystals, the hydration reaction rate is the fastest, and it can also form early strength. The hydration reaction that plays a key role in the strength of the later roadbed material is the process of hydrating dicalcium silicate to generate hydrated calcium silicate gel and calcium hydroxide crystals. The hydration reaction rate is relatively slow. Therefore, in order to improve the performance of the roadbed material, promoting the hydration of dicalcium silicate to generate hydrated calcium silicate gel is the key to further improving the performance of the roadbed material. Therefore, the present invention adds biochar, blast furnace slag, red mud and red gypsum, and the four act synergistically and are compatible with each other to further promote the hydration reaction, thereby preparing a roadbed material with better performance.
[0010] The present invention mainly adds biochar, wherein the biochar is obtained by pyrolysis of biomass, wherein the biochar obtained by pyrolysis of biomass can have a large number of surface functional groups and porous structures, and more surface functional groups and porous structures can absorb the moisture in the roadbed material faster, can retain more water in the gravity drainage balance, have a larger water retention potential and surface area, and reduce the water diffusion rate. In this way, the biochar can further shorten the coagulation time of the roadbed material and accelerate the hardening. Moreover, since it absorbs a large amount of water in the early stage, the biochar can also be used as a curing agent in the later stage of the hydration reaction to release More water is released to further promote the hydration reaction, and the reaction process is more complete, thereby improving the strength of the roadbed material; the addition of blast furnace slag can promote the hydration reaction. As an auxiliary roadbed material, it can well promote the chemical reaction between the cement component in the roadbed material and water, so that the blast furnace slag improves the compressive performance and strength of the roadbed material by promoting the hydration reaction; and in order to further promote the hydration reaction of the roadbed material, the present invention also adds red mud and red gypsum, through the synergistic effect of multiple raw materials, and mutually compatible to prepare a roadbed material with higher compressive performance and water resistance, and greatly reduces the process cost, is simple to operate, and is convenient for large-scale use. Compared with the existing method for preparing roadbed materials with modified red gypsum, the solution provided by the present invention has lower cost and simpler operation, and the prepared roadbed materials have better water resistance and pressure resistance; the red mud added by the present invention can be used as an auxiliary material to promote the activity of blast furnace slag, thereby greatly reducing the hardening time of the roadbed material, and because it contains components such as silicon oxide and aluminum oxide, after mixing, it can reduce the pores and defects in the roadbed material, thereby improving the density of the roadbed material and increasing the strength, and the active ingredients in the red mud can accelerate the hydration reaction during the cement hydration process, produce a large amount of hydroxide, and form new hydration products to fill the roadbed material The pores of the roadbed material can be further improved, and the aluminum oxide in the red mud can release water during the hardening process, thereby preventing the surface of the roadbed material from being over-dried, thereby accelerating the hardening process of the roadbed material and improving the performance of the concrete; and the addition of red gypsum can well avoid the too fast speed of tricalcium aluminate hydration to form hydrated calcium aluminate crystals, thereby producing flash coagulation. The main component of red gypsum is calcium sulfate, which can react well with hydrated calcium aluminate to form calcium sulfonate. Since calcium sulfonate is insoluble in water, it can be well wrapped on the surface of cement clinker to form a protective film, which prevents water from entering the interior of the cement and slows down the hydration reaction, thereby avoiding the flash coagulation phenomenon caused by the hydration of cement clinker. Therefore, it can be known that the present invention mainly prepares a roadbed material with excellent performance by adding biochar, red mud, red gypsum and blast furnace slag, and through the synergistic effect between the four, it promotes the synthesis of hydration reaction while improving the strength.
[0011] Preferably, as a further specific embodiment, the biochar is mainly made from biomass; The biomass is one or more of tobacco straw, wood chips, coffee grounds and corn straw.
[0012] Preferably, as a further specific embodiment, the biomass is a mixture of tobacco straw and coffee grounds.
[0013] Preferably, as a further specific embodiment, the mass ratio of the tobacco straw to the coffee grounds is (1-3): 1; Preferably, the mass ratio of the tobacco straw to the coffee grounds is 1:1.
[0014] Therefore, for the present invention, the selection of biomass is very important. This is because the present invention mainly achieves the modification of red gypsum by adding biochar after pyrolysis of biomass, and cooperates with other various raw materials to prepare a roadbed material with excellent performance. The surface of biochar has a large number of functional groups and porous structures, which can absorb the moisture in the roadbed material more quickly, so that the biochar can further shorten the coagulation time of the roadbed material and accelerate hardening. Moreover, since it absorbs a large amount of moisture in the early stage, the biochar can also act as an internal curing agent in the later stage of the hydration reaction, releasing moisture from the inside of the roadbed material to promote the hydration reaction. and make the reaction process more complete, thereby improving the durability and mechanical strength of the roadbed material. Therefore, after a lot of creative work, the present invention has found that by using a mixture of tobacco straw and coffee grounds, and the mass ratio of tobacco straw and coffee grounds is (1-3):1, preferably when the mass ratio is 1:1, the biochar formed by the biomass obtained by the mixture of the two has more efficient water retention and water absorption after treatment, and can further reduce the water seepage of the modified red stone roadbed material in the early stage of hydration, can greatly shorten the hardening time, and can also release more water when used as an internal curing agent in the later stage, thereby better catalyzing the hydration reaction.
[0015] The present invention also provides a method for preparing the above-mentioned biochar-synergistic multi-source solid waste modified red gypsum roadbed material, which is characterized by comprising the following steps: The biomass is crushed, dried and then pyrolyzed to obtain biochar; The blast furnace slag, red mud and red gypsum are dried and then ground and sieved respectively to obtain blast furnace slag powder, red mud powder and red gypsum powder; Add biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement in sequence, mix well, then add water and stir well.
[0016] Preferably, as a further specific implementation, the specific steps of the pyrolysis are: In N2 Under atmosphere, the temperature is raised to 300-600°C at 5-10°C / min and kept constant for 2-4 hours, then ground through a 100-300 mesh sieve.
[0017] Preferably, as a further specific implementation, the specific steps of pyrolysis are: 2 In an atmosphere, the temperature was raised to 600°C at a rate of 10°C / min and maintained at this temperature for 4 hours, and then ground through a 200-mesh sieve.
[0018] In the preparation method of the present invention, the method of pyrolyzing biomass to prepare biochar is very important. This is because the biochar formed after pyrolysis of biomass has functional groups and pore structures on its surface, so that the biochar itself has excellent water absorption, and the biochar has excellent adsorption characteristics and strong stability. These properties can well promote the hydration reaction of roadbed materials and shorten the hardening time of roadbed materials. Among them, for the present invention, the pyrolysis temperature and the heating rate are very important. This is because for biochar, too high temperature and too fast heating will affect the porosity of the biochar itself. As the pyrolysis temperature increases , the hot volatile matter in the biochar is reduced, the pore diameter and porosity are increased, and the surface area of the biochar is increased. The porosity determines the surface area of the biochar. The larger the surface area of the biochar, the richer the porosity, and the more functional groups it has on its surface. The biochar obtained after pyrolysis will have more surface functional groups and pore structures, so that it can absorb water faster, greatly shorten the coagulation time of the roadbed material, accelerate hardening, and better act as an internal curing agent in the later stage of the hydration reaction to release more water, promote the hydration reaction of the roadbed material, and improve the strength of the roadbed material. Therefore, for the present invention, when the pyrolysis is at N 2 In an atmosphere, the temperature is raised to 300-600°C at a rate of 5-10°C / min and maintained at a constant temperature for 2-4 hours, preferably in N 2 Under the atmosphere, when the temperature is increased to 600℃ at a rate of 10℃ / min and kept constant for 4h, the prepared biochar has excellent performance. This is because the pyrolysis temperature greatly determines the performance of biochar, but if the pyrolysis temperature is too high, the degree of aromatization of biochar will be deepened, the hydrophobicity will be enhanced, and the number of polar functional groups of biochar will be reduced accordingly, resulting in weakened hydrophilicity. The water absorption performance of the biochar obtained after pyrolysis is reduced, making it unable to release more water in the later stage of hydration, affecting the strength of the roadbed material.
[0019] Then, the blast furnace slag, red mud and red gypsum are dried and ground into powders to obtain blast furnace slag powder, red mud powder and red gypsum powder. For the present invention, the mass ratio of biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement is very important. When the mass ratio of biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement is: (1-5): (1-10): (1-10): (60-70): (1-5), preferably when the mass ratio of biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement is 3:10:10:70: 5. When the mass ratio of the solid mixture obtained by mixing biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement to water is 1:(0.6-0.8), preferably 1:0.6, the roadbed material prepared therefrom has excellent performance, and has excellent water resistance and compressive strength. This is because the present invention mainly achieves the purpose of modifying red gypsum by coordinating multiple raw materials such as biochar, blast furnace slag powder and red mud powder, and promotes the reaction between cement and water through the mutual compatibility of these four substances, thereby producing more hydrates and improving the strength and durability of the roadbed material. If too much red gypsum is added, the content of aluminum oxide and silicon oxide will be reduced, thereby reducing the strength of the roadbed material; if too little is added, the red gypsum will not be able to form scale-inhibiting calcium aluminate with calcium aluminate hydrate, thereby wrapping the cement clinker, causing the cement clinker to flash set; and if too much red mud is added, the roadbed material will become frosted, thereby affecting the strength of the roadbed material, while too little red mud will cause the surface of the roadbed material to become overly dry, thereby causing cracks; the main component of blast furnace slag powder is calcium oxide, and if there is too much blast furnace slag powder, there will not be enough active aluminum oxide, silicon oxide and sulfate ions, thereby causing calcium oxide to form calcium hydroxide, and too much calcium hydroxide will affect the strength of the roadbed material to a certain extent, reducing its compressive performance, and if too little blast furnace slag powder is added, the hydration reaction will not be complete, affecting the strength of the roadbed material.
[0020] Preferably, as a further specific implementation, the drying temperature is 80-120° C., and the drying time is 24-48 hours.
[0021] Preferably, as a further specific embodiment, the stirring speed is 300-450 rpm, and the stirring time is 1-5 min; Preferably, the stirring speed is 300 rpm and the stirring time is 3 min.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a biochar-synergistic multi-source solid waste modified red gypsum roadbed material. The biochar-synergistic multi-source solid waste modified red gypsum roadbed material synergizes the four elements of biochar, blast furnace slag, red mud and red gypsum to greatly shorten the coagulation time and make the internal structure of the modified red gypsum roadbed material more compact, with higher water resistance and compression resistance, which can well meet the requirements of road base construction.
[0023] (2) The present invention provides a method for preparing a biochar-synergistic multi-source solid waste-modified red gypsum roadbed material, which comprises crushing and pyrolyzing biomass to obtain biochar having surface functional groups and a porous structure, and optimizing the red gypsum through the biochar-synergistic multi-source solid waste, thereby preparing a roadbed material with better water resistance and higher compressive resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A process flow chart for preparing the biochar-cooperative multi-source solid waste-modified red gypsum roadbed material of the present invention; Figure 2 The unconfined compressive strength diagram of the roadbed materials prepared in Examples 4-7 and Comparative Examples 1-3; Figure 3 Softening coefficient diagram of the roadbed materials prepared in Examples 4-7 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but those skilled in the art will understand that the embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] In order to more clearly explain the technical solution of the present invention, it is described in the form of specific embodiments below.
[0027] Example 1 See also Figure 1 The preparation process of the biochar-cooperative multi-source solid waste-modified red gypsum roadbed material of the present invention is specifically as follows: Tobacco straw from a tobacco company in Kunming, Yunnan Province was used as biomass; The tobacco straw was crushed and dried in an electric constant temperature blast drying oven at 120°C for 48 hours, and then placed in a tubular furnace, and heated at 5°C / min in a nitrogen atmosphere until the temperature reached 300°C and then kept constant for 2 hours. After being kept constant, the mixture was ground and passed through a 100-mesh sieve to obtain biochar for use; Then, the red mud produced by a factory in Wenshan City, Yunnan Province was dried in an electric constant temperature blast drying oven at 80°C for 24 hours, ground with an agate mortar and sieved through a 60-mesh sieve to obtain red mud powder; The red gypsum produced by a smelter in Baise City, Guangxi Zhuang Autonomous Region was dried in an electric constant temperature blast drying oven at 80°C for 24 hours, and ground with an agate mortar to 60 mesh to obtain red gypsum powder; Blast furnace slag from a pig iron smelter in Kunming, Yunnan Province was dried in an electric constant temperature blast drying oven at 80°C for 24 hours, and ground with an agate mortar and passed through a 60-mesh sieve to obtain blast furnace slag powder; Then, the obtained biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement are mixed in a mass ratio of 1:1:1:60:1 to obtain a solid mixture; Water was added to the solid mixture in a mass ratio of 1:0.6, and the mixture was stirred in a stirrer at 300 rpm for 1 min at room temperature to obtain the product.
[0028] Example 2 The preparation process of biochar-synergistic multi-source solid waste modified red gypsum roadbed material is as follows: Take coffee grounds as biomass; The tobacco straw was crushed and dried in an electric constant temperature blast drying oven at 120°C for 48 hours, and then placed in a tubular furnace, and heated at 10°C / min in a nitrogen atmosphere until the temperature reached 600°C and then kept constant for 4 hours. After being kept constant, the mixture was ground and passed through a 300-mesh sieve to obtain biochar for use; Then, the red mud produced by a factory in Wenshan City, Yunnan Province was dried in an electric constant temperature blast drying oven at 120°C for 48 hours, ground with an agate mortar and sieved through a 60-mesh sieve to obtain red mud powder; The red gypsum produced by a smelter in Baise City, Guangxi Zhuang Autonomous Region was dried in an electric constant temperature blast drying oven at 120°C for 48 hours, and ground with an agate mortar to 60 mesh to obtain red gypsum powder; Blast furnace slag from a pig iron smelter in Kunming, Yunnan Province was dried in an electric constant temperature blast drying oven at 120°C for 48 hours, and ground with an agate mortar and passed through a 60-mesh sieve to obtain blast furnace slag powder; Then, the obtained biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement are mixed in a mass ratio of 5:10:10:70:5 to obtain a solid mixture; Water is added to the solid mixture in a mass ratio of 1:0.8, and the mixture is stirred in a stirrer at room temperature at a rotation speed of 450 rpm for 5 minutes to obtain the product.
[0029] Example 3 The preparation process of biochar-synergistic multi-source solid waste modified red gypsum roadbed material is as follows: Coffee grounds and tobacco straw from a tobacco company in Kunming, Yunnan Province were mixed in a mass ratio of 1:1 as biomass; The coffee grounds and tobacco straw were crushed and dried in an electric constant temperature forced air drying oven at 120°C for 48 hours, and then placed in a tubular furnace and heated at 10°C / min in a nitrogen atmosphere until the temperature reached 600°C and then kept constant for 4 hours. After being kept constant, they were ground and passed through a 200-mesh sieve to obtain biochar; Then, the red mud produced by a factory in Wenshan City, Yunnan Province was dried in an electric constant temperature blast drying oven at 80°C for 24 hours, ground with an agate mortar and sieved through a 60-mesh sieve to obtain red mud powder; The red gypsum produced by a smelter in Baise City, Guangxi Zhuang Autonomous Region was dried in an electric constant temperature blast drying oven at 80°C for 24 hours, and ground with an agate mortar to 60 mesh to obtain red gypsum powder; Blast furnace slag from a pig iron smelter in Kunming, Yunnan Province was dried in an electric constant temperature blast drying oven at 80°C for 24 hours, and ground with an agate mortar and passed through a 60-mesh sieve to obtain blast furnace slag powder; Then, the obtained biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement are mixed in a mass ratio of 1:1:1:60:1 to obtain a solid mixture; Water was added to the solid mixture in a mass ratio of 1:0.6, and the mixture was stirred in a stirrer at 300 rpm for 3 minutes at room temperature to obtain the product.
[0030] Example 4 The preparation process of biochar-synergistic multi-source solid waste modified red gypsum roadbed material is as follows: Coffee grounds and tobacco straw from a tobacco company in Kunming, Yunnan Province were mixed in a mass ratio of 1:3 as biomass; The coffee grounds and tobacco straw were crushed and dried in an electric constant temperature forced air drying oven at 120°C for 48 hours, and then placed in a tubular furnace and heated at 10°C / min in a nitrogen atmosphere until the temperature reached 600°C and then kept constant for 4 hours. After being kept constant, they were ground and passed through a 200-mesh sieve to obtain biochar; Then, the red mud produced by a factory in Wenshan City, Yunnan Province was dried in an electric constant temperature blast drying oven at 80°C for 24 hours, ground with an agate mortar and sieved through a 60-mesh sieve to obtain red mud powder; The red gypsum produced by a smelter in Baise City, Guangxi Zhuang Autonomous Region was dried in an electric constant temperature blast drying oven at 80°C for 24 hours, and ground with an agate mortar to 60 mesh to obtain red gypsum powder; Blast furnace slag from a pig iron smelter in Kunming, Yunnan Province was dried in an electric constant temperature blast drying oven at 80°C for 24 hours, and ground with an agate mortar and passed through a 60-mesh sieve to obtain blast furnace slag powder; Then, the obtained biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement are mixed in a mass ratio of 1:1:1:60:1 to obtain a solid mixture; Water was added to the solid mixture in a mass ratio of 1:0.6, and the mixture was stirred in a stirrer at 300 rpm for 3 minutes at room temperature to obtain the product.
[0031] Example 5 The specific implementation method is consistent with Example 3, except that the biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement are mixed in a mass ratio of 3:5:5:65:3.
[0032] Example 6 The specific implementation method is consistent with Example 3, except that the biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement are mixed in a mass ratio of 1:2:2:35:1.
[0033] Example 7 The specific implementation method is consistent with Example 3, except that the biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement are mixed in a mass ratio of 3:10:10:70:5.
[0034] Example 8 The specific implementation method is consistent with Example 7, except that the heating rate of pyrolysis is adjusted to 1°C / min.
[0035] Example 9 The specific implementation method is consistent with Example 7, except that the heating rate of pyrolysis is adjusted to 15°C / min.
[0036] Example 10 The specific implementation method is consistent with Example 7, except that the pyrolysis temperature is adjusted to 200°C.
[0037] Embodiment 11 The specific implementation method is consistent with Example 7, except that the pyrolysis temperature is adjusted to 800°C.
[0038] Example 12 The specific implementation method is consistent with Example 7, except that the biomass is adjusted to corn stalks.
[0039] Example 13 The specific implementation method is consistent with Example 7, except that the biomass is adjusted to tobacco straw.
[0040] Comparative Example 1 The specific implementation method is consistent with Example 6, except that biomass is not used.
[0041] Comparative Example 2 The specific implementation method is consistent with Example 6, except that the blast furnace slag powder is replaced by calcium carbide slag powder.
[0042] Comparative Example 3 The specific implementation method is consistent with Example 6, except that the red mud powder is replaced by carbide slag powder.
[0043] Comparative Example 4 The specific implementation method is consistent with Example 6, except that the biomass is not pyrolyzed but used directly.
[0044] Experimental Example 1 The modified red gypsum roadbed material prepared in Examples 1-10 and Comparative Examples 1-4 is mainly in the form of slurry. The slurry is poured into a Φ50×50mm mold, and demolded after standing at room temperature for 24 hours to obtain a cylindrical test block. The test block is cured under standard curing conditions, and the unconfined compressive strength of the test block is measured at 7 days, 14 days, and 28 days respectively; on the 28th day, the test block is soaked to saturation and dried to test the strength to calculate the softening coefficient. The test data are shown in Table 1.
[0045]
[0046] Experimental Example 2 Take the modified red gypsum roadbed material slurry prepared in Examples 4-7 and Comparative Examples 1-3, pour the slurry into a Φ50×50mm mold, let it stand for 24 hours at room temperature, then demould to obtain a cylindrical test block, and cure it under standard curing conditions. The unconfined compressive strength of the test block is measured at 7 days, 14 days, and 28 days respectively; on the 28th day, soak the test block until saturated and dry it to test the strength to calculate the softening coefficient, where the specific test data are as follows Figure 2 and Figure 3 shown.
[0047] It can be seen from the above table that by comparing Examples 1-7, it can be known that the unconfined compressive strength and softening coefficient of the roadbed material are affected by the addition amount of biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement. In the present invention, the mass ratio of biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement is: (1-5): (1-10): (1-10): (60-70): (1-5). Preferably, when the mass ratio of biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement is 3:10:10:70:5, the roadbed material prepared therefrom has good mechanical strength and water resistance, which can not only meet the engineering requirements of the road base but also meet the resource utilization of solid waste. If the addition amount of red gypsum is too much, the content of aluminum oxide and silicon oxide is reduced. If the amount added is too little, the red gypsum will not be able to form scale-inhibiting calcium aluminate with calcium aluminate hydrate, thereby wrapping the cement clinker and causing the cement clinker to flash. If there is too much red mud, the roadbed material will be frosted, thus affecting the strength of the roadbed material. If there is too little red mud, the surface of the roadbed material will be overly dry and cracked. The main component of blast furnace slag powder is calcium oxide. If there is too much blast furnace slag powder, there will not be enough active alumina, silicon oxide and sulfate, thus causing calcium oxide to form calcium hydroxide. Too much calcium hydroxide will affect the strength of the roadbed material to a certain extent and reduce its compressive performance. If the amount of blast furnace slag powder added is too little, the hydration reaction will not be complete, thus affecting the strength of the roadbed material. Therefore, for the present invention, the present invention mainly adds biochar, red mud, red gypsum and blast furnace slag, through the synergistic effect of the four, and through the control of the mass ratio of each component, the strength of the roadbed material is improved while ensuring that the roadbed material has good durability, water resistance and compression resistance. The mutual compatibility between multiple raw materials promotes hydration reaction synthesis while improving the strength, thereby preparing a roadbed material with excellent performance.
[0048] By comparing Examples 7-11 and Comparative Example 4, it can be known that, for the present invention, the process of forming biochar by pyrolysis of biomass is very important. This is because the biochar formed after pyrolysis of biomass has functional groups and pore structures on its surface, so that the biochar itself has excellent water absorption, and the biochar has excellent adsorption characteristics and strong stability. These properties can well promote the hydration reaction of roadbed materials and shorten the hardening time of roadbed materials. The present invention utilizes the hydrophilicity of biochar formed by biomass after special treatment, and after special treatment, it can have a large number of surface functional groups and porous structures. More surface functional groups and porous structures can absorb the moisture in the roadbed material faster, and can retain more water on the gravity drainage balance, with greater water retention potential and surface area, and reduced water diffusion rate. In this way, the biochar can further shorten the coagulation time of the roadbed material and accelerate hardening. Moreover, since it absorbs a large amount of moisture in the early stage, it can be used in the later stage of the hydration reaction. Biochar can also be used as a curing agent to release more water to further promote the hydration reaction and make the reaction process more complete, thereby improving the strength of the roadbed material. The pyrolysis temperature and the rate of heating are very important. This is because for biochar, too high a temperature and too fast a heating rate will affect the porosity of the biochar itself. As the pyrolysis temperature increases, the hot volatile substances in the biochar decrease, the pore diameter and porosity increase, and the surface area of the biochar increases. Its porosity determines the surface area of the biochar. The larger the surface area of the biochar, the richer the porosity, and the more functional groups it has on its surface. The biochar obtained after pyrolysis will have more surface functional groups and pore structures, so that it can absorb water faster, greatly shorten the coagulation time of the roadbed material, accelerate hardening, and better act as an internal curing agent in the later stage of the hydration reaction to release more water, promote the hydration reaction of the roadbed material, and improve the strength of the roadbed material. Therefore, for the present invention, when the pyrolysis is at N 2 In an atmosphere, the temperature is raised to 300-600°C at a rate of 5-10°C / min and maintained at a constant temperature for 2-4 hours, preferably in N 2 Under the atmosphere, when the temperature is increased to 600℃ at a rate of 10℃ / min and kept constant for 4h, the prepared biochar has excellent performance. This is because the pyrolysis temperature greatly determines the performance of biochar, but if the pyrolysis temperature is too high, the degree of aromatization of biochar will be deepened, the hydrophobicity will be enhanced, and the number of polar functional groups of biochar will be reduced accordingly, resulting in weakened hydrophilicity. The water absorption capacity of the biochar obtained after pyrolysis is reduced, making it unable to release more water in the later stage of hydration, affecting the strength of the roadbed material; if the pyrolysis temperature is too low, the biomass will not be able to completely form biochar, thereby affecting the performance of the roadbed material prepared therefrom.
[0049] By comparing Example 7 with Examples 12-13, it can be known that the addition of biomass is very important for preparing the roadbed material of the present invention. This is because the present invention mainly adds biomass and utilizes the hydrophilicity of the biochar formed by the pyrolysis treatment of the biomass. After special treatment, it can have a large number of surface functional groups and porous structures. More surface functional groups and porous structures can absorb the moisture in the roadbed material faster, can retain more water on the gravity drainage balance, have a larger water retention potential and surface area, and reduce the moisture diffusivity. In this way, the biochar can further shorten the coagulation time of the roadbed material and accelerate the hardening. Moreover, since it absorbs a large amount of moisture in the early stage, the biochar can also be used as a curing agent in the later stage of the hydration reaction to release more moisture to further promote the hydration reaction and make the reaction process more complete, thereby improving the strength of the roadbed material. Therefore, by adding biochar, the present invention can make the prepared roadbed material have higher strength and better compressive resistance.
[0050] By comparing Example 7 with Comparative Examples 2-3, it can be known that the addition of red mud powder and blast furnace slag powder is also very important for the present invention. This is because the present invention mainly promotes the activity of blast furnace slag by adding red mud as an auxiliary material, thereby improving the activity of blast furnace slag. The improvement of the activity of blast furnace slag can further promote the hydration reaction, so that it can be used as an auxiliary material for roadbed materials to promote the chemical reaction between cement components in the roadbed materials and water. The addition of red mud improves the ability of blast furnace slag to promote the hydration reaction, thereby improving the compressive performance and strength of the roadbed material. The hardening time of the roadbed material is greatly reduced. The red mud powder contains silicon oxide, aluminum oxide and other ingredients that can reduce the pores and defects in the roadbed material after mixing, thereby improving the density of the roadbed material and increasing the strength. The active ingredients in the red mud can accelerate the hydration reaction during the cement hydration process, produce a large amount of hydroxide, and form new hydration products to fill the pores in the roadbed material, further improving the density of the roadbed material. The aluminum oxide in the red mud can release water during the hardening process, thereby preventing the surface of the roadbed material from being over-drying, thereby accelerating the hardening process of the roadbed material and improving the performance of the concrete.
[0051] By comparing Example 7 and Comparative Example 4, it can be known that the way of pyrolyzing biomass is very important for the present invention. This is because in the preparation method of the present invention, as the pyrolysis temperature increases, the hot volatile matter in the biochar decreases, the pore diameter and porosity increase, and the surface area of the biochar increases. The porosity determines the surface area of the biochar. The larger the surface area of the biochar, the richer the porosity, and the more functional groups it has on its surface. The biochar obtained after pyrolysis will have more surface functional groups and pore structures, so that it can absorb water faster, greatly shorten the coagulation time of the roadbed material, accelerate hardening, and in the later stage of the hydration reaction, it can better act as an internal curing agent to release more water, promote the hydration reaction of the roadbed material, and improve the strength of the roadbed material.
[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. Biochar synergistic multi-source solid waste modified red gypsum roadbed material, characterized in that: Mainly include biochar, blast furnace slag, red mud, red gypsum, cement and water; The mass ratio of biochar, blast furnace slag, red mud, red gypsum and cement is (1-5): (1-10): (60-70): (1-5); The mass ratio between the mixture of biochar, blast furnace slag, red mud, red gypsum and cement and water is 1: (0.6-0.8).
2. The biochar-synergistic multi-source solid waste modified red gypsum roadbed material according to claim 1 is characterized in that: The mass ratio of the biochar, blast furnace slag, red mud, red gypsum and cement is 3:10:10:70:5; The mass ratio between the mixture of biochar, blast furnace slag, red mud, red gypsum and cement and water is 1:0.
6.
3. The biochar-synergistic multi-source solid waste modified red gypsum roadbed material according to claim 1, characterized in that: The biochar is mainly made from biomass; The biomass is one or more of tobacco straw, wood chips, coffee grounds and corn straw.
4. The biochar-synergistic multi-source solid waste modified red gypsum roadbed material according to claim 3 is characterized in that: The biomass is a mixture of tobacco straw and coffee grounds.
5. The biochar-synergistic multi-source solid waste modified red gypsum roadbed material according to claim 4, characterized in that: The mass ratio of the tobacco straw to the coffee grounds is (1-3):1; Preferably, the mass ratio of the tobacco straw to the coffee grounds is 1:
1.
6. A method for preparing a biochar-coordinated multi-source solid waste-modified red gypsum roadbed material as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: The biomass is crushed, dried and then pyrolyzed to obtain biochar; The blast furnace slag, red mud and red gypsum are dried and then ground and sieved respectively to obtain blast furnace slag powder, red mud powder and red gypsum powder; Add biochar, blast furnace slag powder, red mud powder, red gypsum powder and cement in sequence, mix well, then add water and stir well.
7. The preparation method according to claim 6, characterized in that: The specific steps of the pyrolysis are: Under N2 atmosphere, the temperature was raised to 300-600°C at a rate of 5-10°C / min and kept constant for 2-4 hours, and then ground through a 100-300 mesh sieve.
8. The preparation method according to claim 7, characterized in that: The specific steps of the pyrolysis are: in a N2 atmosphere, the temperature is raised to 600°C at a rate of 10°C / min and kept constant for 4 hours, and then ground through a 200-mesh sieve.
9. The preparation method according to claim 6, characterized in that: The drying temperature is 80-120° C., and the drying time is 24-48 hours.
10. The preparation method according to claim 6, characterized in that: The stirring speed is 300-450rpm, and the stirring time is 1-5min; Preferably, the stirring speed is 300 rpm and the stirring time is 3 min.